Design and in vivo evaluation of ultrafine inorganic-oxide-containing-sunscreen formulations - (:unkn) unknown (My University, 1997)
Ultrafine titanium dioxide, zinc oxide, and a 1:1 mixture of ZnO/TiO2 were used as 5% dispersions in sunscreen formulae. Three different carrier bases were evaluated for their accelerated stability and theological properties with and without metal oxides based on sodium lauryl sulphate/polysorbate 80, triethanolamine stearate, and cetyl trimethyl ammonium chloride. All three bases showed thixotropic behaviour. Addition of metal oxides only affected the magnitude of viscosity not the viscoelastic behaviour. The cationic emulsion base was found to be the most stable to incorporate the microfine metal oxides, the others' viscosity values showing a significant drop in storage. The in vivo sun protection factors were determined on the cationic based emulsions in four human subjects using an UV source covering both UVA-UVB regions. The mean sun protection factors were found to be 5.03, 4.03, and 4.8 for TiO2, ZnO, and 1:1 ZnO/TiO2 respectively for 4 mg·cm-2 applications, the differences not being significant.
Keywords: In vivo SPF; Rheological tests; Sunscreens; Titanium dioxide; Ultrafine metal oxides; Zinc oxide